NEW OPPORTUNITIES FOR THE USE OF DIGITAL TECHNOLOGIES IN ACCOUNTING - Z.M. Shaukerova; D.M. Aykupeshova; I. Zhanimkhan (Academic Journal of Physical and Chemical Sciences, 2019)
Technology accelerates all the industries to which they relate. Most accountants already use digital tools and streamline processes to make them paperless. However, as technology continues to evolve and automate even more numerous functions, conversations are transformed into the prospect of accounting without human participation. In the real world, technologies that transform the financial industry in no way make the human factor redundant. Instead, technologies such as cloud, artificial intelligence (AI), and blockchain will enable accountants - and the entire financial services industry - to reduce manual data entry and improve the speed, accuracy, and quality of data.